(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the quality of education and the diversity of methods and perspectives of development stages.Also, the article shows the processes of teaching and educating the students with the help of what kind of methods in the modern pedagogical situation. The teaching methodology is aimed at activating teaching methods, the process of educational and cognitive activity strengthens it.